UNUSUAL CASE OF COMBINED LARYNGOCELE PRESENTING AS CERVICAL SWELLING: UNUSUAL CASE OF COMBINED LARYNGOCELE PRESENTING AS CERVICAL SWELLING - Jovanović, Anđelina (Medical Research, 2022)
Laryngocele is a sac-like, pathological enlargement of the Morgan's ventricle, which occurs between the true and false vocal cords. This change is filled with air and is continuous with the lumen of the larynx. It is usually asymptomatic and is accidentally detected during radiological diagnosis. We present the case of a 54-year-old patient who came for an examination due to a painless swelling in her neck on the left side, which lasted for 8 months and increased on Valsalva's maneuver. Occasionally the patient was hoarse. By clinical otorhinolaryngological examination and computed tomography of the neck and larynx, we found a cystic formation, filled with air, which extended above the larynx and spread to the side of the neck. We completely surgically removed the laryngocele with an external cervical approach. The neck of the laryngocele is sent through the thyroid membrane, while preserving the upper laryngeal nerve and the accompanying vascular stalk. Pathohistological examination revealed that the laryngocele consists of respiratory layered cylindrical epithelium. Laryngocele is in most of the cases a benign change. Sometimes they may be associated with laryngeal cancer or may be misinterpreted during radiological diagnosis as malignancy.